7th drug hypersensitivity meeting: part one. Issue 3 (August 2016) - Carr, Daniel; Chung, Wen-Hung; Jenkiins, Rosalind; Chaponda, Mas; Nwikue, Gospel; Cornejo Castro, Elena; Antoine, Daniel; Pirmohamed, Munir; Wuillemin, Natascha; Dina, Dolores; Eriksson, Klara; Yerly, Daniel; et al.
Table of contents Oral Abstracts O1 Functionally distinct HMGB1 isoforms correlate with physiological processes in drug-induced SJS/TEN Daniel F. Carr, Wen-Hung Chung, Rosalind E. Jenkiins, Mas Chaponda, Gospel Nwikue, Elena M. Cornejo Castro, Daniel J. Antoine, Munir Pirmohamed O2 Hypersensitivity reactions to beta-lactams, does the t cell recognition pattern influence the clinical picture? Natascha Wuillemin, Dolores Dina, Klara K. Eriksson, Daniel Yerly O3 Specific binding characteristics of HLA alleles associated with nevirapine hypersensitivity Rebecca Pavlos, Elizabeth Mckinnin, David Ostrov, Bjoern Peters, Soren Buus, David Koelle, Abha Chopra, Craig Rive, Alec Redwood, Susana Restrepo, Austin Bracey, Jing Yuan, Silvana Gaudieri, Mary Carrington, David Haas, Simon Mallal, Elizabeth Phillips O4 Do we need to measure total ige for the interpretation of analytical results of ImmunoCAP dnd 3gAllergy specific IgE? Douwe De Boer, Paul Menheere, Chris Nieuwhof, Judith Bons O5 Neutrophil activation in systemic anaphylaxis: results from the multicentric NASA study Friederike Jonsson, Luc De Chaisemartin, Vanessa Granger, Caitlin Gillis, Aurelie Gouel, Catherine Neukirch, Fadia Dib, Pascale Roland Nicaise, Dan Longrois, Florence Tubach, Sylvie Martin, Pierre Bruhns, NASA Study Group O6 Purpuric drug eruptions due to epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) for non-small-cell lung cancer (NSCLC): a clinic-pathological study of 32 cases Kai-Lung Chen, Shu-Ling Liao, Yi-Shuan Sheen, Yung-Tsu Cho, Che-Wen Yang, Jau-Yu Liau, Chia-Yu Chu Poster presentations: Poster Walk 1—Anaphylaxis (P01–P09) P1 Anaphylactic reactions during anaesthesia and the perioperative period Rita Aguiar, Anabela Lopes, Natália Fernandes, Leonor Viegas, M. A. Pereira-Barbosa P2 Anaphylaxis to chlorhexidine: is there a cross-reactivity to alexidine? Antonia Bünter, Nisha Gupta, Tatjana Pecaric Petkovic, Nicole Wirth, Werner J. Pichler, Oliver Hausmann P3 Cefotaxime-induced severe anaphylaxis in a neonate Mehtap Yazicioglu, Pinar G. Ozdemir, Gokce Ciplak, Ozkan Kaya P4 Clinical features and diagnosis of anaphylaxis resulting from exposure to chlorhexidine Peter John Cooke P5 Drug-induced anaphylaxis: five-year single-center survey Inês Mota, Ângela Gaspar, Filipe Benito-Garcia, Marta Chambel, Mário Morais-Almeida P6 Intraoperative severe anaphylactic reaction due to patent blue v dye Luis Marques, Eva Alcoceba, Silvia Lara P7 Kounis syndrome in the setting of anaphylaxis to diclofenac Leonor Carneiro-Leão, Carmen Botelho, Eunice Dias-Castro, Josefina Cernadas P8 Perioperative anaphylaxis audit: Royal Melbourne Hospital Katherine Nicholls, William Lay, Olivia Smith, Christine Collins, Gary Unglik, Kymble Spriggs, Priscilla Auyeung, Jeremy McComish, Jo A. Douglass P9 Recurrent peri-operative anaphylaxis: a perfect storm Jonny G. Peter, Paul Potter Poster Walk 2: DH regions and patient groups (P10–P19) P10 A rare presentation of amoxicillin allergy in a young child Fabrícia Carolino, Eunice Dias De Castro, Josefina R. Cernadas P11 Adverse drug reactions in children: antibiotics or virus? Ana Sofia Moreira, Carmo Abreu, Eva Gomes P12 Allergic reactions in invasive medical procedures Bárbara Kong Cardoso, Elza Tomaz, Sara Correia, Filipe Inácio P13 Antibiotic allergy in children: room for improvement Annabelle Arnold, Natasha Bear, Kristina Rueter, Grace Gong, Michael O'Sullivan, Saravanan Muthusamy, Valerie Noble, Michaela Lucas P14 Drug hypersensitivity reactions in children and results of diagnostic evaluation Neringa Buterleviciute, Odilija Rudzeviciene P15 Nonimmediate cutaneous drug reactions in children: are skin tests required? Ana Sofia Moreira, Carmo Abreu, Eva Gomes P16 Pediatric patients with a history of penicillin allergy and a positive penicillin skin test may not be at an increased risk for multiple drug allergies Sara May, Thanai Pongdee, Miguel Park P17 Proved hypersensitivity to drugs according data of Vilnius University Hospital Santariskiu Klinikos Linas Griguola, Arturas Vinikovas, Simona Kašinskaite, Violeta Kvedariene P18 Self-reported prevalence of drug hypersensitivity reactions among students in Celal Bayar University, Turkey Ayse Aktas, Suheyla Rahman, Huseyin Elbi, Beyhan Cengiz Ozyurt P19 Severe drug hypersensitivity reactions in pediatric age Ozlem Cavkaytar, Betul Karaatmaca, Pinar Gur Cetinkaya, Saliha Esenboga, Umit M. Sahiner, Bulent E. Sekerel, Ozge Soyer Poster Walk 3: Desensitisation (P20–P28) P20 A protocol for desensitisation to valaciclovir Celia Zubrinich, Bianca Tong, Mittal Patel, Michelle Giles, Robyn O'Hehir, Robert Puy P21 A rare case of desensitization to modafinil Josefina Cernadas, Luís Amaral, Fabrícia Carolino P22 A sixteen-day desensitization protocol in delayed type hypersensitivity reactions to oral drugs Semra Demir, Asli Gelincik, Muge Olgac, Raif Caskun, Derya Unal, Bahauddin Colakoglu, Suna Buyukozturk P23 Desensitization to intravenous etoposide using a 12 and a 13-step protocol. Two cases report Olga Vega Matute, Amalia Bernad, Gabriel Gastaminza, Roselle Madamba, Carlos Lacasa, M. J. Goikoetxea, Carmen D'Amelio, Jose Rifón, Nicolas Martínez, Marta Ferrer P24 Drug desensitisation in oncology: the experience of an immunoallergology department for 5 years Carmelita Ribeiro, Emília Faria, Cristina Frutuoso, Anabela Barros, Rosário Lebre, Alice Pego, Ana Todo Bom P25 Filgrastim anaphylaxis: a successful desensitization protocol Luis Amaral, Josefina Cernadas P26 Galsulfase hypersensitivity and desensitization of a mucopolysaccharidosis VI patient Luis Felipe Ensina, Carolina Aranda, Ines Camelo Nunes, Ana Maria Martins, Dirceu Solé P27 Rapid drug desensitization with biologicals: one-center experience with four biologicals Sevim Bavbek, Resat Kendirlinan, Pamir Çerçi, Seda Tutluer, Sadan Soyyigit, Zeynep Çelebi Sözener, Ömür Aydin, Reyhan Gümüsburun P28 Successful desensitization to a high dose of methotrexate in a delayed type hypersensitivity reaction Josefina Cernadas, Leonor Carneiro-Leão, Fabrícia Carolino, Marta Almeida Poster Walk 4: SJS (P29–P38) P29 Assessment of impact of infection on drug-induced severe cutaneous adverse reactions and rhabdomyolysis using the Japanese adverse drug event report database Kimie Sai, Takuya Imatoh, Ryosuke Nakamura, Chisato Fukazawa, Yasushi Hinomura, Yoshiro Saito P30 Characterization of erythema multiforme and severe cutaneous adverse reactions hospitalizations Bernardo Sousa-Pinto, Cláudia Correia, Lídia Gomes, Sara Gil-Mata, Luís Araújo, Luís Delgado P31 Effects of infection on incidence/severity of SJS/TEN and myopathy in Japanese cases analyzed by voluntary case reports Ryosuke Nakamura, Kimie Sai, Takuya Imatoh, Yoshimi Okamoto-Uchida, Koji Kajinami, Kayoko Matsunaga, Michiko Aihara, Yoshiro Saito P32 Efficacy of tumor necrosis factor—a antagonists in Stevens–Johnson syndrome and toxic epidermal necrolysis: a randomized controlled trial and immunosuppressive effects evaluation Chuang-Wei Wang, Shih-Chi Su, Shuen-Iu Hung, Hsin-Chun Ho, Chih-Hsun Yang, Wen-Hung Chung P33 Evolution of drug causality in Stevens–Johnson syndrome and toxic epidermal necrolysis in Europe: analysis of 10 years RegiSCAR-Study Maren Paulmann, Ariane Dunant, Maja Mockenhaupt, Peggy Sekula, Martin Schumacher, Sylvia Kardaun, Luigi Naldi, Teresa Bellón, Daniel Creamer, Cynthia Haddad, Bruno Sassolas, Bénédicte Lebrun-Vignes, Laurence Valeyrie-Allanore, Jean-Claude Roujeau P34 Long-term sequelae in patients with Stevens–Johnson syndrome and toxic epidermal necrolysis: a 5-year analysis Maren Paulmann, Carmen Kremmler, Peggy Sekula, Laurence Valeyrie-Allanore, Luigi Naldi, Sylvia Kardaun, Maja Mockenhaupt P35 Major emotional complications and decreased health related quality of life among survivors of Stevens–Johnson syndrome and toxic epidermal necrolysis Roni P. Dodiuk-Gad, Cristina Olteanu, Anthony Feinstein, Rena Hashimoto, Raed Alhusayen, Sonia Whyte-Croasdaile, Yaron Finkelstein, Marjorie Burnett, Shachar Sade, Robert Cartotto, Marc Jeschke, Neil H. Shear P36 Retrospective analysis of Stevens–Johnson syndrome and toxic epidermal necrolysis in Japanese patients: treatment and outcome Naoko Takamura, Yumiko Yamane, Setsuko Matsukura, Kazuko Nakamura, Yuko Watanabe, Yukie Yamaguchi, Takeshi Kambara, Zenro Ikezawa, Michiko Aihara P37 Severe physical complications among survivors of Stevens–Johnson syndrome and toxic epidermal necrolysis Roni P. Dodiuk-Gad, Cristina Olteanu, Rena Hashimoto, Hall Chew, Raed Alhusayen, Sonia Whyte-Croasdaile, Yaron Finkelstein, Marjorie Burnett, Shachar Sade, Robert Cartotto, Marc Jeschke, Neil H. Shear P38 Stevens–Johnson syndrome/toxic epidermal necrolysis combined with haemophagocytic lymphohistiocytosis: a case report Brittany Knezevic, Una Nic Ionmhain, Allison Barraclough, Michaela Lucas, Matthew Anstey Poster Walk 5: Other organs/unexpected immune reactions (P39–P47) P39 A case report of patient with anti-tuberculosis drug-related severe liver failure Toru Usui, Xiaoli Meng, John Farrell, Paul Whitaker, John Watson, Neil French, Kevin Park, Dean Naisbitt P40 Acute interstitial nephritis induced by ibuprofen Ana Castro Neves, Susana Cadinha, Ana Moreira, J. P. Moreira Da Silva P41 Cetuximab induced acneiform rash—two case reports Daniela Ledic Drvar, Sandra Jerkovic Gulin, Suzana Ljubojevic Hadzavdic, Romana Ceovic P42 Enteropathy associated with losartan Ana Montoro De Francisco, Talía De Vicente Jiménez, Amelia García Luque, Natalia Rosado David, José Mª Mateos Galván P43 Granuloma annulare after therapy with canakinumab Razvigor Darlenski P44 Hypersensitivity eosinophilic myocarditis or acute coronary syndrome? Case report Dario Gulin, Jozica Sikic, Jasna Cerkez Habek, Sandra Jerkovic Gulin, Edvard Galic P45 Piperacillin-induced immune haemolytic anaemia: a severe and frequent complication of antibiotic treatment in patients with cystic fibrosis Philip Specht, Doris Staab, Beate Mayer, Jobst Roehmel P46 Progesterone triggered pemphigus foliaceus: case report Sandra Jerkovic Gulin, Caius Solovan, Anca Chiriac P47 Ramipril: triggered generalized pustular psoriasis Paola Djurinec, Kresimir Kostovic, Mirna Bradamante, Sandra Jerkovic Gulin, Romana Ceovic Poster Walk 6: NSAIDs (P48–P56) P48 Aspirin desensitization in cardiovascular disease—Portuguese experience Jose Pedro Almeida, Joana Caiado, Elisa Pedro, Pedro Canas Da Silva, Manuel Pereira Barbosa P49 Asthma and/or rhinitis to NSAIDs with good tolerance to ASA Gador Bogas, Natalia Blanca-López, Diana Pérez-Alzate, Inmaculada Doña, José Augusto Agúndez, Elena García-Martín, José Antonio Cornejo-García, Cristobalina Mayorga, María José Torres, Gabriela Canto, Miguel Blanca P50 Clinical characteristics of 196 patients with non-steroidal anti-inflammatory drug (NSAIDs) hypersensitivity Sengül Aksakal, Aytül Zerrin Sin, Zeynep Peker Koç, Fatma Düsünür Günsen, Ömür Ardeniz, Emine Nihal Mete Gökmen, Okan Gülbahar, Ali Kokuludag P51 Development of immediate hypersensitivity to several NSAIDs maintaining good tolerance to ASA Natalia Pérez-Sánchez, Natalia Blanca-López, Diana Pérez-Alzate, Gador Bogas, Inmaculada Doña, María Salas, María José Torres, Miguel Blanca, Gabriela Canto P52 Diagnosis of hypersensitivity reactions to paracetamol in a large series of cases Inmaculada Doña, Maria Salas, Francisca Gomez, Natalia Blanca-Lopez, Diana Perez-Alzate, Gador Bogas, Esther Barrionuevo, Maria Jose Torres, Inmaculada Andreu, Miguel Ángel Miranda, Gabriela Canto, Miguel Blanca P53 Hypersensitivity to paracetamol according to the new classification of hypersensitivity to NSAIDs Gabija Didžiokaite, Olesia Gaidej, Simona Kašinskaite, Violeta Kvedariene P54 Ibuprofen and other aryl propionic derivates can induce immediate selective hypersensitivity responses Diana Perez-Alzate, Natalia Blanca-López, Maria Isabel Garcimartin, Inmaculada Doña, Maria Luisa Somoza, Cristobalina Mayorga, Maria Jose Torres, Gador Bojas, Jose Antonio Cornejo-Garcia, Maria Gabriela Canto, Miguel Blanca P55 Subjects developing immediate responses to several NSAIDs can be selective with good tolerance to ASA Natalia Blanca-Lopez, Diana Pérez-Alzate, Francisco Javier Ruano Perez, Inmaculada Doña, Maria Luisa Somoza, Inmaculada Andreu, Miguel Angel Miranda, Cristobalina Mayorga, Maria Jose Torres, Jose Antonio Cornejo-Garcia, Miguel Blanca, Maria Gabriela Canto P56 Utility of low-dose oral aspirin challenges for diagnosis of aspirin exacerbated respiratory disease Elina Jerschow, Teresa Pelletier, Zhen Ren, Golda Hudes, Marek Sanak, Esperanza Morales, Victor Schuster, Simon D. Spivack, David Rosenstreich Poster Walk 7: NSAID 2 (P57–P65) P57 Alternate regulation of cyclooxygenase-2 (COX-2) MRNA expression may predispose patients to aspirin-induced exacerbations Renato Erzen, Mira Silar, Nissera Bajrovic, Matija Rijavec, Mihaela Zidarn, Peter Korosec P58 Anaphylaxis to diclofenac: what about the underlying mechanism? Leonor Carneiro-Leão, Fabrícia Carolino, Luís Amaral, Carmen Botelho, Eunice Dias-Castro, Josefina Cernadas P59 COX-2 inhibitors: are they always a safe alternative in hypersensitivity to nonsteroidal anti-inflammatory drugs? Luis Amaral, Fabricia Carolino, Eunice Castro, Josefina Cernadas P60 Management of patients with history of NSAIDs reactions prior to coronary angioplasty Mona Al-Ahmad, Tito Rodriguez P61 Oral drug challenge with non-steroidal anti-inflammatory drug under spirometric control: clinical series of 110 patients João Pedro Azevedo, Emília Faria, Beatriz Tavares, Frederico Regateiro, Ana Todo-Bom P62 Prevalence and incidence of analgesic hypersensitivity reactions in Colombia Pablo Andrés Miranda, Bautista De La Cruz Hoyos P63 Recent endoscopic sinus surgery lessens reactions during aspirin challenge in patients with aspirin exacerbated respiratory disease Teresa Pelletier, Waleed Abuzeid, Nadeem Akbar, Marc Gibber, Marvin Fried, Weiguo Han, Taha Keskin, Robert Tamayev, Golda Hudes, Simon D. Spivack, David Rosenstreich, Elina Jerschow P64 Safe use of imidazole salycilate in a case of multiple NSAIDs induced urticaria-angioedema Elisa Boni, Marina Russello, Marina Mauro P65 Selective hypersensitivity reactions to ibuprofen—seven years experience Marta Ferreira Neto Poster Walk 8: Epidemiological methods (P66–P72) P66 Allopurinol hypersensitivity: a 7-year review Lise Brosseron, Daniela Malheiro, Susana Cadinha, Patrícia Barreira, J. P. Moreira Da Silva P67 Antibiotic allergy labelling is associated with increased hospital readmission rates in Australia Brittany Knezevic, Dustin Sprigg, Michelle Trevenen, Jason Seet, Jason Trubiano, William Smith, Yogesh Jeelall, Sandra Vale, Richard Loh, Andrew Mclean-Tooke, Michaela Lucas P68 Experts' opinions on severe cutaneous adverse drug reactions-report of a survey from the 9th international congress on cutaneous adverse drug reactions 2015 Roni P. Dodiuk-Gad, Cristina Olteanu, Wen-Hung Chung, Neil H. Shear P69 HLA-A*31-positive AGEP with carbamazepine use and other severe cutaneous adverse drug reactions (SCARs) detected by electronic medical records screening Sabine Müller, Ursula Amstutz, Lukas Jörg, Nikhil Yawalkar, Stephan Krähenbühl P70 Patients with suspected drug allergy: a specific psychological profile? Eunice Dias-Castro, Ana Leblanc, Laura Ribeiro, Josefina R. Cernadas P71 Use of an electronic device and a computerized mathematic algorithm to detect the allergic drug reactions through the analysis of heart rate variability Arantza Vega, Raquel Gutierrez Rivas, Ana Alonso, Juan Maria Beitia, Belén Mateo, Remedios Cárdenas, Juan Jesus Garcia-Dominguez P72 Variation in ERAP influences risk for HLA-B*57:01 positive abacavir hypersensitivity Rebecca Pavlos, Kaija Strautins, Ian James, Simon Mallal, Alec Redwood, Elizabeth Phillips Poster Walk 9: DRESS/AGEP (P73–P81) P73 A clinical case of DRESS syndrome in a child after administration of amoxicillin-clavulanic acid Rita Aguiar, Anabela Lopes, Ana Neves, Maria Do Céu Machado, M. A. Pereira-Barbosa P74 Acute generalized exanthematous pustulosis (AGEP) induced by mesalazine, reliable and oftenly used drug to treat inflammatory bowel disease Ceyda Tunakan Dalgiç, Emine Nihal Mete Gökmen, Fatma Düsünür Günsen, Gökten Bulut, Fatma Ömür Ardeniz, Okan Gülbahar, Ali Kokuludag, Aytül Zerrin Sin P75 Changes of blood plasmacytoid dendritic cells, myeloid dendritic cells, and basophils during the acute stage of drug reaction with eosinophilia and systemic symptoms (DRESS) and other drug eruptions Shao-Hsuan Hsu, Yung-Tsu Cho, Che-Wen Yang, Kai-Lung Chen, Chia-Yu Chu P76 Characterization of isoniazid/rifampicin-specific t-cell responses in patients with DRESS syndrome Young-Min Ye, Gyu-Young Hur, Hae-Sim Park, Seung-Hyun Kim P77 DRESS syndrome secondary to sulfasalazine with delayed TEN: a case presentation Syed Ali, Michaela Lucas, Peter N. Hollingsworth, Andrew P. C. Mclean-Tooke P78 Drug rash with eosinophilia and systemic symptoms (DRESS) features according to the culprit drug Zohra Chadly, Nadia Ben Fredj, Karim Aouam, Haifa Ben Romdhane, Naceur A. Boughattas, Amel Chaabane P79 Drug reaction with eosinophilia and systemic symptoms induced by allopurinol: not always easy to diagnose Marina Lluncor Salazar, Beatriz Pola, Ana Fiandor, Teresa Bellón, Elena Ramírez, Javier Domínguez Ortega, Santiago Quirce, Rosario Cabañas P80 Drug reaction with eosinophilia and systemic symptoms syndrome induced by two drugs simultaneously: a case report Krasimira Baynova, Marina Labella, Manuel Prados P81 The drug reaction with eosinophilia and systemic symptoms (DRESS) induced by the second-line antituberculosis drugs and Epstein–Barr virus infection Agne Ramonaite, Ieva Bajoriuniene, Brigita Sitkauskiene, Raimundas Sakalauskas Poster Walk 10: Miscellaneous drug hypersensitivity (P82–P91) P82 A case of cycloserine-induced lichenoid drug eruption confirmed with a lymphocatye transformation test Jae-Woo Kwon, Shinyoung Park P83 Allergic reaction to topical eye drops: 5 years' retrospective study in a drug allergy unit Diana Silva, Leonor Carneiro Leão, Fabricia Carolino, Eunice Castro, Josefina Cernadas P84 Allergy to heparins Diana Perez-Alzate, Natalia Blanca-López, Maria Luisa Somoza Alvarez, Maria Garcimartin, Maria Vazquez De La Torre, Francisco Javier Ruano Pérez, Elisa Haroun, Gabriela Canto Diez P85 Allopurinol-induced adverse drug reactions Katinka Ónodi-Nagy, Ágnes Kinyó, Lajos Kemény, Zsuzsanna Bata-Csörgo P86 Analysis of a population with immediate hypersensitivity to corticosteroids: an 11 year review Joana Sofia Pita, Emília Faria, Rosa Anita Fernandes, Ana Moura, Nuno Sousa, Carmelita Ribeiro, Carlos Loureiro, Ana Todo Bom P87 Anaphylaxis against mivacurium in a 12-months old boy at first-time exposure Wolfgang Pfützner P88 Antihistamine-exacerbated chronic spontaneous urticaria: a paradox? Nadine Marrouche, Clive Grattan P89 Anti-osteoporotic agents-induced cutaneous adverse drug reactions in Asians Yu-En Chen, Chun-Bing Chen, Wen-Hung Chung, Yu-Ping Hsiao, Chia-Yu Chu P90 Diagnosis of allergic reactions to eye drops Maria Vazquez De La Torre, Natalia Blanca-Lopez, Diana Perez-Alzate, Maria Isabel Garcimartin, Francisco Javier Ruano, Maria Luisa Somoza, Elisa Haroun, Gabriela Canto P91 Diagnostic approach in suspected hypersensitivity reactions to corticosteroids Fabrícia Carolino, Eunice Dias De Castro, Josefina R. Cernadas